An interventive study of the effects of therapeutic lifestyle changes and simvastatin on the insulin sensitivity status of non obese hyperlipidaemic - Yaacob, Nor Azwany (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2009)
making it important to look into the insulin resistance in a group of non-obese hyperlipidaemic subjects. This study was designed to determine insulin sensitivity and secretory status of non-obese normoglycaemic subjects, and to find out the relationship between hyperlipidaemia and insulin sensitivity in a non-obese population. ln addition, the second phase of this study looked at the effects of lipid lowering interventions on insulin sensitivity in hyperlipidaemic subjects. A cross sectional study involving 246 nonobese (BMI<25 kg/m2 ), waist circumference male<] 02cm, female <88cm) and nondiabetic subjects aged between 30-60 years was carried out. The subjects underwent OGTT, LFT and RFT to exclude type 2 diabetes, !GT, IFG, renal and liver diseases. Fasting plasma glucose, fasting insulin and lipid profile were measured. Insulin sensitivity and secretory status were computed using the homeostasis model assessment (HOMA) software to obtain HOMA%S, HOMA%B and HOMA-IR. The subjects were divided into two groups according to their lipid status and their insulin sensitivity was compared between the two groups. Two groups of 28 non-obese hyperlipidaemic and 28 normolipidaemic subjects participated in the intervention study. They underwent 3 months of therapeutic lifestyle changes (TLC) regimen after which they were again divided into TLC and Simvastatin groups and for the subsequent three months went through either TLC only or TLC plus Simvastatin. Finally their insulin sensitivity and lipid status were assessed again. The hyperlipidaemic subjects showed substantially lower insulin sensitivity and higher insulin resistance in comparison to normolipidaemic subjects. The adjusted mean of HOMA%S of hyperlipidaemic and normolipidaemic subjects were 80 and 155 (p<0.0001) respectively. Insulin secretory status as expressed '"> th~ mea;- c.~ Lff1MA %'- '~~ 0 178 ~,,.~ ! l r. for hynPrlipidaemic :mrl nnrmolipir:lae:,,ic subjects respectively. It mdicates that the B cells of hyperlipidaemic subjects have to secrete more insulin to overcome the Jowered msuim sens1bv1ty. Intervention by both TLC and Simvastatin showed significant reduction of insulin resistance (62.3% improvement of HOMA-IR in TLC group and 51.44% in Simvastatin and TLC group) and improvement of insulin sensitivity (142% improvement of HOMA%S in TLC group and 122% in Simvastatin and TLC group) in hyperlipidaemic subjects with reduction of lipid levels. It can thus be concluded that, insulin sensitivity of otherwise healthy nonobese hyperlipidaemic subjects is lower than normolipidaemic subjects. Therapeutic life style ch~nges is able to improve the insulin sensitivity in this group of subjects.